Analysis Of Market Structure And Profitability In The 10 Largest Banks In Indonesia Using The Structure Conduct Performance Method - Lestari, Sri Puji; Mardanugraha, Eugenia (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to analyze the influence of market structure on the profitability of the largest commercial banks in Indonesia during the 2021–2024 period. The main focus of the study is on the relationship between market concentration (CR), market share (MS), and its interaction with Return on Assets (ROA), with the Structure-Conduct-Performance (SCP) approach. The research method used a descriptive quantitative approach with panel data analysis on the 10 largest banks, covering more than 65% of the assets of the national banking industry. The estimation model used is the Random Effect Model, with control variables such as Loan to Deposit Ratio (LDR), total assets (ASSET), cost efficiency (CIR), and non-performing loans (NPL). The results showed that the CR and MS variables generally had a negative effect on ROA, while control variables such as LDR and ASSET had a significant positive effect. The interaction between MS and CR (MSCR) is also negative, suggesting that market dominance in a concentrated structure is not always advantageous. Implicitly, a bank's profitability is influenced more by operational efficiency and risk management than market forces. Therefore, regulators are advised to focus on improving efficiency through stricter supervisory policies, instead of encouraging market concentration as a means of improving banking performance.